Crisis del capitalismo-imperialista; la que se nos avecina: se desinfla la burbuja especulativa en todo el mundo (2007)
ABSTRACT: The crisis of the capitalist system throughout the world is no longer a prognosis but evidence that fail to conceal. It is slow, progresses slowly, but is also very deep and widespread, and will be extended further, reaching all sectors of society in a way dramatic. There is no country that is not shaken by it. Capitalism has no future, even in the short term.